BS EN 2942. Aerospace series. Insert, MJ screw thread, helical coil, self-locking tanged insertion drive, in heat resisting nickel base alloy NI-PH2801 (Inconel X750), silver plated. (16th March 2022) - British Standards Institution,
No abstract available